AB0468 Possible effects of belimumab therapy on t- and b-cell phenotype in a cohort of patients with systemic lupus erythematosus. (15th June 2017) - Piantoni, S; Regola, F; Scarsi, M; Dall'Ara, F; Andreoli, L; Tincani, A; Airò, P
Abstract : Background: B- and T-cell activation are one of the pathogenic mechanisms of systemic lupus erythematosus (SLE). After repeated antigenic stimulation, T-cells undergo different modifications, leading to the differentiation into effector memory T-cells (CCR7-CD45RA-) and highly experienced memory T-cells (CCR7-CD45RA+). Similarly, down-modulation of CD28 may lead to the expansion of the CD28neg T-cells, a subpopulation with peculiar effector activities (1). Recent studies showed that memory CD4+ T-cells are increased in the peripheral blood of SLE patients, whereas contradictory data are reported on CD28 neg T-cells (2). Peripheral transitional B-cells (38high24high) are immature B-cells transiting to secondary lymphoid organs, where their maturation into follicular or marginal zone B-cells is driven by a stimulating factor called BLyS. This population is expanded in patients with SLE (3). The anti-BLyS therapy agent belimumab is approved for treatment of SLE. Objectives: The aims of this study were to characterize B- and T-cell phenotype in a cohort of patients with SLE, according with disease activity, and to analyse their modifications therapy with belimumab. Methods: Phenotypic analysis of peripheral blood B and T lymphocytes was made by flow-cytometry. First, a cross-sectional study on 51 consecutive SLE patients (F/M: 48/51; median age: 35 years; anti-dsDNA: 16 UI/ml; C3: 79 mg/dl; C4: 10 mg/dl) was performed. Second, 18 patients treated with belimumab were longitudinally followed. Disease activity was evaluated by SLEDAI-2K score. Results: SLE patients were divided in two groups according disease activity: patients with SLEDAI-2K ≥6 (n:13) had a higher percentage of circulating CD4+T-cells with CD28neg phenotype: median value (25th-75th percentile)=13 (5–19) vs 3 (1–5) % of CD4+ T-cells, p<0.01), as well as of those with an effector memory (37 (29–40) vs 18 (12–27) % of CD4+ T-cells, p<0.01), highly experienced memory phenotype (9 (7–12) vs 1 (1–3) % of CD4+ T-cells, p<0.01), and of B-cells with a transitional phenotype (3 (0.5–5) vs 0.2 (0–0.4) % of CD19+ cells, p=0.02), in comparison with patients with low disease activity (n:38). After 6 months of treatment with belimumab, no significant variation in the T-cell subset was observed, but there was a reduction in the number of circulating naïve B-cells (from 49 (30–71) to 21 (11–36) % of CD19+ cells; p<0.01). Among these patients, the proportion of transitional B-cells, was raised (as compared with normal controls) at baseline in 3/11 patients with SLEDAI-2K ≥6, and 0/7 with low disease activity. After 6 month of therapy, their number normalized in 2 of these 3 patients. Conclusions: CD4+ T-cells subpopulations displaying phenotype characteristics of effector lymphocytes, and transitional B-cells are expanded in peripheral blood of patients with active SLE. Therapy with belimumab may inhibit the production of transitional and naïve B-cells. References: Strioga M, et al. Immunology 2011. Ugarte-Gil M, et al. Lupus 2016. Jacobi AM, et al. Arthritis Rheum 2008. Disclosure of Interest: None declared